2005
DOI: 10.1002/jctb.1266
|View full text |Cite
|
Sign up to set email alerts
|

Continuous precipitation of calcium sulfate dihydrate from waste sulfuric acid and lime

Abstract: • C and 80• C is suitable for further processing for construction plaster. In a precipitation process with pure sulfuric acid only single perfect needle-like crystals occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 19 publications
(23 reference statements)
4
19
0
Order By: Relevance
“…Chemical precipitation is a widely used, proven technology for the removal of metals and other inorganic compounds, suspended solids, fats, oils, greases, and some other organic substances (including organophosphates) from wastewater (U.S. EPA, 2000). Previous investigators have reported successful reduction of soluble sulfate from water by formation of calcium aluminate and sulfoaluminates (Schaezier, 1978), and from pure and waste sulfuric acid/lime suspension by formation of calcium sulfate (Gominšek et al, 2005). Chemical precipitation through the addition of barium or calcium salts is an alternative, mainly if applied to the treatment of wastewaters that contain high sulfate concentrations.…”
Section: Introductionmentioning
confidence: 97%
“…Chemical precipitation is a widely used, proven technology for the removal of metals and other inorganic compounds, suspended solids, fats, oils, greases, and some other organic substances (including organophosphates) from wastewater (U.S. EPA, 2000). Previous investigators have reported successful reduction of soluble sulfate from water by formation of calcium aluminate and sulfoaluminates (Schaezier, 1978), and from pure and waste sulfuric acid/lime suspension by formation of calcium sulfate (Gominšek et al, 2005). Chemical precipitation through the addition of barium or calcium salts is an alternative, mainly if applied to the treatment of wastewaters that contain high sulfate concentrations.…”
Section: Introductionmentioning
confidence: 97%
“…the terminal calcium concentrations for both 1:1 and 2:1 ratios after 90 min reaction time. Due to reasons previously explained, Na 3 PO 4 was not used and kinetics measurements were not conducted for the 2:1 experiments, as it was expected to be faster, as described by Gominsek et al (2005). As expected, an excess of 2:1 precipitant at 80°C achieved much lower aqueous calcium concentration.…”
Section: Experimental Investigation Of the Batch Precipitation Kineticsmentioning
confidence: 93%
“…MnCO 3 and kutnahorite (MnCa(CO 3 ) 2 ) formation was previously reported under reductive conditions and in aerated systems (Bamforth et al 2006;Waybrant et al 1998). Soluble SO 4 2-was removed from water by precipitation with pure sulfuric acid/lime suspension forming CaAl 2 O 4 , sulfoaluminate, and CaSO 4 (Gominsek et al 2005;Schaezler 1978). Sulfate can also be removed by the addition of barium or calcium salts; this requires additional solid phase separation and disposal.…”
Section: Precipitationmentioning
confidence: 98%